A MODEL OF ACCRUAL MEASUREMENT WITH IMPLICATIONS FOR THE EVOLUTION OF THE BOOK-TO-MARKET RATIO - Ryan, Sg (Journal of Accounting Research, 1995)
Accruals, Book-to-Market ratio, Predictive ability, Abnormal earnings